A Newbie at the RDAP Summit, or How I Learned that the RDAP Summit is for Everyone - Joanna Thielen (Journal of eScience Librarianship, 2018)
This commentary describes the thoughts and perceptions of a first-time attendee to the Research Data Access and Preservation (RDAP) Summit in March 2018. The author describes her initial hesitations to attend this conference as a data librarian from a medium-sized institution. But after attending, she is convinced that the RDAP Summit is for anyone interested in data, including librarians that work at medium- and small-sized institutions. After describing the format of the Summit, the highlights of attending are described, including gathering ideas related to all aspects of research data management, access, and preservation; hearing data management perspectives from outside of academic libraries; networking opportunities for the extrovert and introvert; and opportunities to connect with librarians at similar universities and with similar interests.